Sustainable masonry: stability and behavior of structures - Ciblac, Thierry; Morel, Jean-Claude (Mechanical engineering and solid mechanics series, 2014)
This book covers the impact of sustainable masonry on the environment, touting the many benefits of utilizing local and/or low embodied energy materials in the construction of sustainable buildings.